2023
DOI: 10.1021/acs.jpca.3c00562
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Excited-State Dynamics of DNA-Templated Monomers and Aggregates of Asymmetric Polymethine Dyes

Katelyn M. Duncan,
Hannah M. Byers,
Madaline E. Houdek
et al.

Abstract: Aggregates of conjugated organic molecules (i.e., dyes) may exhibit relatively large one- and two-exciton interaction energies, which has motivated theoretical studies on their potential use in quantum information science (QIS). In practice, one way of realizing large one- and two-exciton interaction energies is by maximizing the transition dipole moment (μ) and difference static dipole moment (Δd) of the constituent dyes. In this work, we characterized the electronic structure and excited-state dynamics of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…In addition, the covalently conjugated chromophores complexes serve as excellent model systems for constructing controlled molecular aggregates scaffolded on DNA and investigating their optical properties, , delocalized excitation state, coherent nature, and energy transfer process. Cyanine dyes like Cy3 and Cy5 and indolenine dyes such as squaraine are frequently employed to explore dynamics of exciton within the J-like dimer and H-like tetramer templated on varying DNA structures. This approach facilitates a comprehensive understanding of multiple intermolecular interactions within the DNA-scaffolded multichromophore complex, unraveling both interchromophore interactions (electronic couplings) and interactions between chromophores with their environment (system-bath coupling) . Another example is merocyanine, which is incorporated onto the phosphodiester backbone of varied nucleic acids as the nucleobase mimic.…”
Section: Optical Nanomaterials Directed By Designer Dna Nanostructuresmentioning
confidence: 99%
“…In addition, the covalently conjugated chromophores complexes serve as excellent model systems for constructing controlled molecular aggregates scaffolded on DNA and investigating their optical properties, , delocalized excitation state, coherent nature, and energy transfer process. Cyanine dyes like Cy3 and Cy5 and indolenine dyes such as squaraine are frequently employed to explore dynamics of exciton within the J-like dimer and H-like tetramer templated on varying DNA structures. This approach facilitates a comprehensive understanding of multiple intermolecular interactions within the DNA-scaffolded multichromophore complex, unraveling both interchromophore interactions (electronic couplings) and interactions between chromophores with their environment (system-bath coupling) . Another example is merocyanine, which is incorporated onto the phosphodiester backbone of varied nucleic acids as the nucleobase mimic.…”
Section: Optical Nanomaterials Directed By Designer Dna Nanostructuresmentioning
confidence: 99%
“…Further, a dye can be tethered to a specific site of DNA via a variety of covalent linkers, thus enabling control over the number of dyes and their positions relative to the DNA. 30 These advantages of dye covalent templating via DNA enabled exciton delocalization in aggregates of such dye families as azo dyes, 31–33 merocyanines, 34 polymethine dyes, 35–43 squaraines, 44–48 and perylenes. 49 While several studies have shown that aggregates of porphyrins, 50–54 the most related dye family to bacteriochlorins, can be covalently templated via DNA, the extent of exciton delocalization was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we explored if a fully synthetic DNA-templated bacteriochlorin dimer can exhibit exciton delocalization. We employed a specific type of branched DNA structure, a 4-arm DNA construct known as a Holliday Junction (HJ) that was previously shown to template a variety of dyes via a post-modification of the HJ core 36,43,47 and was shown to be particularly advantageous in solubilizing hydrophobic molecules. 47 For the dye, we synthesized a novel analog of Bchl a using a de novo bacteriochlorin methodology developed by Lindsey.…”
Section: Introductionmentioning
confidence: 99%
“…DNA nanostructure-based dye complexes offer exceptional functionality and hold immense potential across various fields, including light-harvesting, energy transfer, , sensing, imaging, and cancer diagnosis. Programmable DNA nanostructures provide a high degree of order and addressability, allowing precise control over the position, orientation, dynamics, and environment of dye molecules. ,,,, Consequently, DNA nanostructures serve as excellent templates for dye assembly, facilitating the creation of highly organized and densely packed supramolecular aggregates. For example, DNA nanostructures have been employed as chiral templates to impart chirality to dye aggregates. More recently, a study reported that benzothiazole cyanine dye K21 and pseudoisocyanine (PIC) can form H-aggregates and J-aggregates on DNA templates, utilizing the exciton transfer properties of strongly coupled J-aggregates for long-range energy transfer. , However, the regulation of fluorescent dye organization on DNA frameworks remains challenging due to a limited understanding of the assembly factors involved.…”
mentioning
confidence: 99%